OP0006 Eular evidence-based recommendations on the management of medium to high dose systemic glucocorticoid therapy in rheumatic diseases. (23rd January 2014) - Duru, N.; van der Goes, M.C.; Jacobs, J.W.; Andrews, T.; Boers, M.; Buttgereit, F.; Caeyers, N.; Cutolo, M.; Halliday, S.; da Silva, J.A.; Kirwan, J.R.; Ray, D.; et al.
Abstract : Objectives: To develop recommendations for the management of medium to high dose systemic glucocorticoid (GC) therapy in rheumatic diseases. Methods: A multidisciplinary EULAR task force was formed, comprising of 8 rheumatologists, 1 endocrinologist, 1 rheumatologist–epidemiologist, 4 patients and 2 research fellows from 7 European countries. Each participant contributed 10 propositions describing key clinical points concerning the safe use of medium to high dose GCs. The final recommendations were developed using a Delphi consensus approach and the wording was improved by a native speaker. A systematic literature search of PUBMED, EMBASE and Cochrane Library was used to identify the best available research evidence to support each of the propositions. The strength of recommendation was given according to research evidence, clinical expertise and patient preference. Results: The 10 final propositions included the topics patient education and informing general practitioners, preventive measures for osteoporosis, optimal GC starting dosages, risk-benefit ratio of GC treatment, GC sparing therapy, screening for co morbidity, and monitoring for adverse events. Most of the propositions were only indirectly supported by evidence from literature. The strength of each recommendation differed according to the level of evidence and clinical expertise, but was generally low because available literature on medium to high dose GC therapy was limited. Conclusions: Ten recommendations for the management of medium to high dose systemic GC therapy in rheumatic diseases were formulated, and strengths of recommendation were provided. Robust evidence was often lacking and items in need for further research were defined. Disclosure of Interest: None Declared